The challenge of Inspection of Education in Spain - Castán Esteban, José Luis (Avances en Supervisión Educativa, 2016)
The Inspectorate of Education only makes sense if it contributes to improving education in our country. And all international studies agree that teachers are the principal value of an education system.The paper discusses examples of three education inspectorates that have elements that can make us reflect: the one Sweden part, through the Onderwijsinspectie, Holland, with its service Skolinspektionen, and the United Kingdom, with Ofsted: Office for Standards in Education, Children's Services and Skills.As a consequence of this study, two types of proposals are made. First, in relation to the improvement in the selection and training of inspectors. Secondly, it is proposed that apart from administrative tasks, inspection focus their time and effort in teacher evaluation.
Keywords: international studies; inspection; evaluation teaching